Conservação de goiaba cv. Paluma com utilização de biofilme comestível - Ramos, Anamaria Ribeiro Pereira; Barbosa, Antonio Carlos de Assis; Silva, Eduardo Ferreira da; Souza, Edvandro Manoel de; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (My University, 2014)
This study aimed to evaluate the quality and shelf life of postharvest fruits of guava, using cassava starch and wax. The fruits were harvested when the skin color of the stadium went "dark green" to "green light". The treatments were: control, cassava starch 1%, 2%, 3% and wax 50%, with 6 repetitions, 3 fruits per plot and 7 assessments. After applying the treatments, the fruits were packed in cardboard boxes and stored at room temperature. The analysis carried out were: soluble solids (SS), titratable acidity (TA), SS / TA, firmness, pH and weight loss (g). The experimental design was completely randomized in a 5 x 7 (days after harvest treatments X) with 6 replications and 3 fruit per plot. Means were compared by Tukey test at 5% probability were performed and regression analysis. The treatments with cassava starch and wax, showed no significant difference in firmness. The loss of mass, cassava starch 3% and carnauba wax were the treatments that showed the best results. In these experimental conditions, the cassava starch and 3% wax delayed fruit ripening and the film formed by these products provided the best look and better conservation, making the fruit more appealing visually.

Esse trabalho objetivou avaliar a qualidade e a vida útil pós-colheita de frutos de goiaba, utilizando fécula de mandioca e cera de carnaúba. Os frutos foram colhidos quando a coloração da casca passava do estádio “verde escuro” para “verde-claro”. Os tratamentos utilizados foram: testemunha, fécula de mandioca 1%, 2%, 3% e cera de carnaúba 50%, com 6 repetições, 3 frutos por parcela e 7 avaliações. Após a aplicação dos tratamentos, os frutos foram acondicionados em caixas de papelão e armazenados à temperatura ambiente. As análises foram: sólidos solúveis (SS), acidez titulável (AT), relação SS/AT, firmeza da polpa, pH e perda de massa (g). O delineamento estatístico foi inteiramente casualizado, em esquema fatorial 5 x 7 (dias após a colheita X tratamentos) com 6 repetições e 3 fruto por parcela. As médias foram comparadas pelo teste Tukey a 5% de probabilidade e foram realizadas análises de regressão. Os tratamentos com fécula de mandioca e cera de carnaúba, não apresentaram diferença significativa quanto à firmeza da polpa. A fécula de mandioca a 3% e cera de carnaúba retardaram o amadurecimento dos frutos e a película formada por estes produtos proporcionou melhor aspecto e melhor conservação, tornando o fruto mais atraente visualmente.
Conservation of guava cv. Paluma with use of biofilm
Keywords: Psidium guajava; Post-harvest; Carnauba wax; Cassava starch; Psidium guajava; Pós-colheita; Cera de carnaúba; Fécula de mandioca